Pengaruh Pendapatan Asli Daerah Dan Dana Alokasi Umum Terhadap Belanja Daerah Dan Pertumbuhan Ekonomi Di Provinsi Sumatera Utara - Amanda Revalina Br Ginting Ginting; Dewi Purnama Sari Br Marbun; Puty Andiny; Safuridar Safuridar; Yani Rizal (EL-EMIR Institute, 2025)
This study aims to analyze the effect of Local Own-Source Revenue (PAD) and the General Allocation Fund (DAU) on Regional Expenditure and Economic Growth in North Sumatra Province. The study uses time series data covering the period from 2010 to 2024, obtained from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). The research method employed is a quantitative approach using path analysis to identify both direct and indirect effects among the variables examined. The results show that Local Own-Source Revenue has a positive but insignificant effect on regional expenditure, while the General Allocation Fund has a positive and significant effect on regional expenditure. Furthermore, Local Own-Source Revenue and regional expenditure are proven to have a positive and significant effect on economic growth in North Sumatra Province. In contrast, the General Allocation Fund shows a negative and significant effect on economic growth. Indirectly, both PAD and DAU influence economic growth through regional expenditure as an intervening variable. These findings indicate that increasing PAD and managing DAU effectively and efficiently can strengthen regional fiscal capacity and promote sustainable economic growth in North Sumatra Province